Optimalisasi Kompetensi Produksi Konten Digital Berbasis Smartphone Untuk Mendukung Publikasi Pengawasan Pemilu dan Pilkada - I Gusti Ngurah Aan Darmawan; Roni Han Wasisto; I Gusti Agung Ngurah Agung Yudha Pramiswara; Niluh Wiwik Eka Putri; Ketut Yuniati; I Gede Teguh Heriawan (Forum Kerjasama Pendidikan Tinggi, 2026)
The development of digital communication requires public institutions to effectively utilize social media as a medium for publication, documentation, and information dissemination to the public. Bawaslu Buleleng Regency, as an election supervisory institution, has a substantial need for documentation and publication activities to support participatory election supervision campaigns, electoral education, and the dissemination of information related to election and regional election oversight. However, digital publication management still faces several challenges, including limited human resources in the public relations division, inadequate smartphone-based digital content production skills, and the suboptimal utilization of smartphones as tools for institutional documentation and publication activities. This community service program aimed to optimize smartphone-based digital content production competencies among the staff and employees of Bawaslu Buleleng Regency in supporting the documentation and publication of election and regional election oversight activities. The methods employed included partner needs assessment, digital visual communication training, smartphone photography and videography training, demonstrations, hands-on practice, and evaluation through pre-tests and post-tests. The results indicated an improvement in participants’ understanding and skills in smartphone-based digital content production. The average pre-test score of 58.57 increased to 92.86 in the post-test, representing an improvement of 58.5%. Furthermore, participants were able to apply photography, videography, and basic editing techniques using smartphones to produce more effective publication content for institutional social media platforms. These findings demonstrate that smartphone-based digital content production training is effective in enhancing human resource capacity to support election and regional election oversight publication through digital media.